Modified western blot with recombinant antigens for serological differentiation between HTLV-I and HTLV-II - Chironna, M; Quarto, M; Germinario, C; Fontana, A (The New microbiologica, 1994)
Some epidemiological and clinical features of HTLV-I and HTLV-II infections remain unclear due to the inability to confirm and distinguish between the two retroviruses. Since HTLV-I and HTLV-II have a high degree of genomic and aminoacid sequence homology, serologic crossreactions are frequent, making it difficult to establish an accurate serologic diagnosis. To confirm and differentiate HTLV-I/II infections, different serologic confirmatory assays were compared. Fourteen serum samples from 11 IVDU, a bisexual subject, a polytransfused and an ATL patient were examined. The sera repeatedly reactive by Elisa and indeterminate with a conventional Western Blot with viral lysate, were retested by new modified Western Blots containing recombinant antigens. All sera from IVDU but one were confirmed and typed as HTLV-II while serum from ATL was serologically typed as HTLV-I. Serum from the polytransfused patient was not confirmed while serum from the bisexual remained indeterminate. These findings suggest that recombinant antigens are useful for serological diagnosis of HTLV-I/II infections.